RECOVERED MEMORIES OF ABUSE IN MENTAL ILLNESSES (Proceedings of the Global Public Health Conference, 2021)
In most mental illnesses, abuse is considered an etiological factor, as asignificantly high number of patients report memories of being abused. Yet, there is also astrong evidence base which suggests that recovered memories can be highly unreliable andthat they can be creations of the current cognitive biases of individuals. Borderlinepersonality disorder and dissociative disorders have long been linked to a history of abuse.In the current paper, the author discusses three patients; two diagnosed with Borderlinepersonality disorder and the other diagnosed with a dissociative identity disorder. Thesepatients were treated by the author in the private sector and analysis of the weeklytreatment records were used for the findings of the current paper. All these patients werefemales who started treatment in their teenage years. All exhibited a treatment-resistantclinical picture and experienced many short-spaced relapses. After the lapse of about sixmonths into psychotherapy, they accidentally discovered a strong memory of an abuseincident, which could not be traced to any known circumstances of their lives. Thememory was highly unlikely to have occurred in reality. Yet, the discovery of the memoryand subsequent cognitive processing of the implications and the visual content of thesememories marked a notable improvement in the patient. With further treatment, all threewere in the remission stage. Therefore, the author feels that patients may have abusivememories, which may or may not be necessarily linked to real life circumstances, yet maystrongly influence the patient’s symptoms. However, despite the validity of thesememories, it is clear that these memories should be treated as significant by clinicians whotreat mental illnesses.
Keywords: mental illnesses; abusive memories; psychotherapy; recovered memories